Efficient removal of sulfamethazine by a magnetic recoverable CeO2/Fe3O4/natural zeolite catalyst in catalytic ozonation process - Guo, Zhuang; Lv, Yifan; Wei, Jian; Zhang, Jiali; Song, Yonghui (Frontiers in Environmental Science, 2023)
In order to realize the efficient removal of sulfamethazine (SMZ) and overcome the recycling difficulty of catalysts in a heterogeneous catalytic ozonation process, low-cost natural zeolite loaded with CeO2 and Fe3O4 (FC/HZ) was synthesized by the co-precipitation method. The FC/HZ catalyst could completely degrade SMZ and realize 39.6% removal of TOC through catalytic ozonation. Moreover, the FC/HZ catalyst exhibited high catalytic ozonation activity under a wide pH range and possessed excellent recyclability (>90%) and stability with a magnet. Based on experiment and material characterization, the possible catalytic mechanism and degradation pathway of SMZ was revealed. In brief, this study offered an effective strategy for preparing recyclable catalysts and eliminating SMZ in aqueous solution.